2011
DOI: 10.1021/am200233k
|View full text |Cite
|
Sign up to set email alerts
|

PVK/MWNT Electrodeposited Conjugated Polymer Network Nanocomposite Films

Abstract: The facile preparation of poly (N-vinyl carbazole) (PVK) and multiwalled carbon nanotubes (MWNTs) solution and conjugated polymer network (CPN) nanocomposite film is described. The stable solutions of PVK/MWNT were prepared in mixed solvents by simple sonication method, which enabled successful deaggregation of the MWNTs with the polymer matrix. MWNT was most effectively dissolved in N-cyclohexyl-2-pyrrolidone (CHP) compared to other solvents like N-methyl pyrrolidone (NMP), dimethyl formamide, and dimethyl su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…PVKZrO 2 composite IR spectrum is almost identical to that of the PVK with similar peaks with a slight shift in the stretching bands, which indicates that some interaction exists between PVK and nano-ZrO 2 . The main characteristic peaks of the PVK backbone are assigned as follows: 1222, 1450 and 1478 cm −1 are attributed to C-C stretching of the vinyl carbazole and vinylidene groups respectively [32,33]. The characteristic absorption band corresponding to ring vibration of NVC moiety was found to be 1448 cm −1 [33,34].…”
Section: B Atr-ir Spectroscopy Studiesmentioning
confidence: 95%
“…PVKZrO 2 composite IR spectrum is almost identical to that of the PVK with similar peaks with a slight shift in the stretching bands, which indicates that some interaction exists between PVK and nano-ZrO 2 . The main characteristic peaks of the PVK backbone are assigned as follows: 1222, 1450 and 1478 cm −1 are attributed to C-C stretching of the vinyl carbazole and vinylidene groups respectively [32,33]. The characteristic absorption band corresponding to ring vibration of NVC moiety was found to be 1448 cm −1 [33,34].…”
Section: B Atr-ir Spectroscopy Studiesmentioning
confidence: 95%
“…By using the nanoindentation method for these epoxy nanocomposites [32], it was found that modification with nanoparticles did not always enhance the stiffness of the epoxy coatings. The presence of nano-SiO 2 in epoxy coatings increased Young's modulus up to 20 times, whereas nanoclay and nano-Fe 2 O 3 modified samples showed ∼30% and ∼25% decrease, relative to the unmodified epoxy coating, respectively.…”
Section: Tensile and Impact Propertiesmentioning
confidence: 99%
“…For organic matrix, called polymer-based nanocomposite, the most used polymers for preparation of nanocomposite coating can be listed as follows: epoxy [2][3][4][5][6][7], polyurethane [8,9], Chitosan [10,11], polyethylene glycol (PEG) [12][13][14][15], polyvinylidene fluoride (PVDF) [16], PANi [17][18][19], PPy [20][21][22][23], polystyrene [24], polyamic acid and polyimide [25], rubber-modified polybenzoxazine (PBZ) [26], polymers containing reactive trimethoxysilyl (TMOS) [27], pullulan [28], fluoroacrylic polymer [29,30], ethylene tetrafluoroethylene (ETFE) [31], polyacrylate [3], poly(N-vinyl carbazole) [32], polycarbonate [33], fluorinated polysiloxane [34], polyester [35], polyacrylic [36], polyvinyl alcohol (PVA) [37], polydimethylsiloxane [38], polyamide [39], and UV-curable polymers [40].…”
Section: Materials For Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The perylene content was investigated and it was found that the UTF with 1.5 wt% perylene (weight ratio of perylene/ PVK) gave strong blue luminescence (Supporting Information, Figure S1,S2). The assembly process of the (1.5 wt% perylene@PVK/LDH) n UTFs was monitored by UV-vis absorption spectroscopy, which showed that the intensities of the absorption bands at about 234-296 and 345 nm (the π − π * and n − π * transitions for the carbazole group of PVK [ 14 ] ) increase linearly with the cycle number ( n ) ( Figure 1 A), indicating a stepwise and regular fi lm-growth process, which was also the case for the (PVK/LDH) n UTFs (Supporting Information, Figure S3a). In contrast, the UTFs-n show weak absorption peaks at 420 nm and 445 nm, originating from the π − π * transition of the fused ring of the perylene molecule [ 15 ] (Supporting Information, Figure S3b), which implies that the perylene has been encapsulated into the LDH interlayers by the PVK carrier.…”
Section: Doi: 101002/adma201203040mentioning
confidence: 99%